2014
DOI: 10.1093/nar/gku160
|View full text |Cite
|
Sign up to set email alerts
|

Kub5-Hera, the human Rtt103 homolog, plays dual functional roles in transcription termination and DNA repair

Abstract: Functions of Kub5-Hera (In Greek Mythology Hera controlled Artemis) (K-H), the human homolog of the yeast transcription termination factor Rtt103, remain undefined. Here, we show that K-H has functions in both transcription termination and DNA double-strand break (DSB) repair. K-H forms distinct protein complexes with factors that repair DSBs (e.g. Ku70, Ku86, Artemis) and terminate transcription (e.g. RNA polymerase II). K-H loss resulted in increased basal R-loop levels, DSBs, activated DNA-damage responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
82
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(96 citation statements)
references
References 57 publications
14
82
0
Order By: Relevance
“…Defects in RPRD1B expression or knockdown cause a deficiency in DNA repair mechanisms known to be critical in resolving cisplatin-induced lesions (47). Consistent with our data indicating low levels of RPRD1B being associated with CisIPN, knockdown of this gene in a breast cancer cell line, MDA-123 results in increased sensitivity to cisplatin (45). However, the suggestive association of RPRD1B with docetaxel-induced neuropathy, indicates that other mechanisms may be important.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Defects in RPRD1B expression or knockdown cause a deficiency in DNA repair mechanisms known to be critical in resolving cisplatin-induced lesions (47). Consistent with our data indicating low levels of RPRD1B being associated with CisIPN, knockdown of this gene in a breast cancer cell line, MDA-123 results in increased sensitivity to cisplatin (45). However, the suggestive association of RPRD1B with docetaxel-induced neuropathy, indicates that other mechanisms may be important.…”
Section: Discussionsupporting
confidence: 91%
“…RPRD1B codes for Kub5-Hera, a protein regulating the binding of RNA polymerase II to CCND1 gene (cyclin D1), and regulating the transcription of several genes involved in the cell cycle (44). Emerging data indicate that RPRD1B plays an important role in several DNA repair mechanisms, including double-strand breaks (DSB) repair through the association with core non-homologous end joining (NHEJ) proteins (45) and mismatch repair (46). Defects in RPRD1B expression or knockdown cause a deficiency in DNA repair mechanisms known to be critical in resolving cisplatin-induced lesions (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mutagenic processes will include replication and transcription fork stalling and the emergence of highly persistent RNA:DNA:RNA hybrids (R-loops) (Aguilera and García-Muse, 2012). Repair of these multiple-damaged sites will require simultaneous functioning DNA repair systems, including DNA nucleotide excision repair, base excision repair, single-strand annealing, homologous recombination (HR), non-homologous end joining (NHEJ), alternative-NHEJ, and newly identified RNA transcription termination factors (RTTFs), including RPRD1B (Kub5/Hera), RPRD1A (p15RS), PSF, XRN2, and SETX (Aguilera and García-Muse, 2012; Helmrich et al, 2013; Morales et al, 2014; Richard et al, 2013). Currently, facility constraints limit our knowledge of: (i) the exact nature of the complex DNA damage created by GCRs; (ii) how such complex lesions are repaired; and most importantly, (iii) what role GCRs play in carcinogenic risk, particularly in gender-specific manners (Morales et al, 2015).…”
Section: Issues Unique To Gcr Simulationmentioning
confidence: 99%
“…Additionally, recent studies also revealed that CREPT could stabilize the binding of β-catenin/TCF4 complex to the promoters of cyclin D1 and c-Myc, which enforced the effects of Wnt canonical signaling on cell cycle [10]. Besides the enhancement on tumorigenesis, CREPT also plays a critical role in the activation of peripheral T cells, keratinocyte differentiation and metastasis by regulating cell cycle-related genes [11]. Since all these effector genes down-stream to CREPT also participate in a wide array of biological processes, the interference on CREPT expression is suggested to be an approach regulating multiple cell behaviors and functions [1215].…”
Section: Introductionmentioning
confidence: 99%